Cara Pengelolaan Limbah Kopi - Halimatussa’diyah, Enni; Fadilla., Audia; Rahma, Alya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Coffee (Coffea sp.) is a plantation product that plays a significant part in the economic development of Indonesians since it can generate significant foreign exchange. Finding out how to control trash from many parts of products created by people in Indonesia is the main goal of this publication. Utilizing qualitative research with the chosen sort of literature study is the chosen research methodology. The study's findings demonstrate that Indonesian coffee waste contains many benefits that can be utilized by local residents. With a different way of managing each product produced, both in terms of managing coffee into cascara tea, coffee cherries into coffee jam, coffee into animal feed, coffee pulp into organic manure, processing coffee waste into compost. Keywords: Coffee Waste, Coffee Waste Management, Benefits of Coffee Waste.